OPPORTUNITIES AND CHALLENGES ASSOCIATED WITH AI-BASED DIGITAL TECHNOLOGIES USAGE FOR AGRICULTURAL EXTENSION SERVICES IN NIGERIA - Olanike Fasilat DEJI; Michael FAMAKINWA; Ebunoluwa Oyindamola FANIYI; Toyin Femi OJO; Aanuoluwapo Oladipupo OPAYINKA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Digitalization of agriculture has been identified as panacea to the problem of food security to teeming population, although its uses for agricultural extension services is still evolving and challenging among extension professionals. This study examined the opportunities and challenges of using AI-based digital tools for agricultural extension services in Nigeria; the study described the socioeconomic characteristics of extension professionals and identified the effects of its usage on extension service delivery. An online questionnaire was used to gather primary data from 131 agricultural extension professionals drawn across the states in Nigeria. Frequency counts, percentages and means were used to analyse and summarize the data collected. The result reveals that majority (75.6%) were male with a mean age of 48.1±15.8 years. The respondents mostly identified provision for real-time insights into the farms and landscape (97.7%) and provision of reliable farm data (75.6%) as the major opportunities for AI-based Digital tools for agricultural extension service, while lengthy technology adoption Process (94.7%) and higher technical skills (70.2%) were the major challenges identified with the use of AI-based digital tools for agricultural extension services by the respondents. The study also reveals that respondents mostly indicated timely enhancement of communication (88.5%) and provision of an update on best practices globally (64.1%) as the key effects of AI-based digital for agricultural extension services. The study recommends that capacity building of extension professionals and farmers; involvement of farmers and other agriculture value chain stakeholders in the development of digital technologies; as well as provision of digital infrastructures and enablers which are germane for digitalization and utilisation of AI-based digital tools for agricultural extension service delivery in Nigeria.